Single molecule magnets of cobalt and zinc homo- and heterometallic coordination polymers prepared by a one-step synthetic procedure. Issue 73 (21st December 2020) - Portolés-Gil, Núria; Gómez-Coca, Silvia; Vallcorba, Oriol; Marbán, Gregorio; Aliaga-Alcalde, Núria; López-Periago, Ana; Ayllón, José A.; Domingo, Concepción
Abstract : One-pot synthesis of heterometallic (Zn(ii )/Co(ii )) nodes directing CP magnetic behaviour to single molecule magnets. Abstract : The synthesis of 1D cobalt and zinc monometallic and heterometallic coordination polymers (CPs) was carried out applying one-pot synthetic methods by using either supercritical carbon dioxide or ethanol as the solvent. A collection of four 1D CPs were thus obtained by the combination of a metal (or a mixture of metals) with the linker 1, 4-bis(4-pyridylmethyl)benzene. The used metallic complexes were zinc and cobalt hexafluoroacetylacetonate, which can easily incorporate pyridine ligands in the coordination sphere of the metal centre. Independently of the used solvent, the precipitated phases involving Zn(ii ), i.e., homometallic CP of Zn(ii ) and bimetallic CP of Zn(ii )/Co(ii ), were isostructural. Contrarily, homometallic CPs of Co(ii ) were precipitated as an isostructural phase of Zn(ii ) or with a different structure, depending on the used solvent. All the structures were resolved by XRD using synchrotron radiation. In addition, the magnetic properties of the new CPs involving Co(ii ) were studied. Remarkably, at low temperatures with the application of an external field, they acted as field-induced single molecule magnets.